2012
DOI: 10.1039/c2sm06999g
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the lipid-bilayer: interaction of polymers and nanoparticles with membranes

Abstract: Membranes can be fabricated either from lipid or polymer molecules, leading to the formation of liposomes or polymersomes. In all types of liposomal membranes, the issue of phase separation plays a central role not only in the membrane-formation itself, but also in the resulting structural features taking place within or at the surface of such membranes. When nanoparticles or polymers interact with lipid membranes, the final morphology is strongly determined by the charge, composition and size of the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
189
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(200 citation statements)
references
References 174 publications
(200 reference statements)
8
189
1
2
Order By: Relevance
“…32 The higher polymer hydrophobicity, the tighter membrane association can be obtained. This is consistent with our recent report that the main driving force for the association of PP75 with the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) monolayer model membrane is the hydrophobic interaction.…”
Section: Effect Of Polymer Amphiphilicitymentioning
confidence: 99%
“…32 The higher polymer hydrophobicity, the tighter membrane association can be obtained. This is consistent with our recent report that the main driving force for the association of PP75 with the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) monolayer model membrane is the hydrophobic interaction.…”
Section: Effect Of Polymer Amphiphilicitymentioning
confidence: 99%
“…In particular transmission, scanning and cryogenic transmission electron microscopies (TEM, SEM and Cryo-TEM), atomic force microscopy (AFM) and fluorescence microscopy are in routine use [94][95][96][97]. Depending on the NP material, size and charge, these techniques allow us to directly investigate different mechanisms of interaction (eg absorption or permeation) by locating the NP position with respect to the membrane and to directly observe the consequences for the membrane, such as changes in permeability or its complete disruption [98].…”
Section: Observing the Np-lipid Bilayer Interactionmentioning
confidence: 99%
“…6 It has been shown that non-specific interactions with the NPs can alter SLB structure and elasticity. 5 NPs can adhere to the lipid bilayer and cause changes in the lipid phase, 7 induce formation of lipid domains [8][9] or pores and extract lipids 10 inducing lipid bilayer disruption. [11][12] Physical chemical properties of NPs, 5,13 such as size, 4,11,[14][15] charge 12,16 and surface chemistry [17][18][19][20] are the main factors modulating NP-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%